THE ESSENCE OF VARIOUS SPORTS GAMES - Dexqonov Baxodir Burxonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
During the period of independence, Uzbek athletes have been achieving high results in international competitions and world championships, as well as in the Olympic Games. Depending on the achievements of our athletes on the international arena, the highest places of the awarded. One of the factors that lead countries to the world is their achievements in physical culture and sports. Of course, in order to achieve these results, great responsibility and perseverance are required from our athletes. In our society, great attention is paid to the training of young athletes, the construction of modern sports facilities, and the holding of many international competitions in our country.